Menciptakan Musuh Imajiner: Penolakan Pengungsi Rohingya di Aceh - Zahlul Pasha Karim; Rahmah Zakia (Badan Strategi Kebijakan Hukum, 2025)
The rejection of Rohingya refugees in Aceh at the end of 2023 led to various negative narratives that shaped an unfavorable image of this group in the eyes of the local community. This research argues that such rejection occurred because of the portrayal of Rohingya Refugees as a threat to society. There are two questions addressed: (1) how did social media contribute to the construction of an imaginary enemy against Rohingya refugees in Aceh?; and (2) what factors drove the shift in the attitude of the Acehnese people from solidarity to rejection? This research is conducted descriptively from various sources of literature, social media content, and news in the mass media. It also borrows the netnography method developed by Kozinets to examine the culture and communities that emerge in computer-mediated communication (social media). The findings reveal that rejection of Rohingya refugees occurs in three forms: negative sentiment expressed on social media platforms, media reports of criminal acts committed by refugees, and the perception that the Rohingya refugees were morally problematic. This phenomenon is underpinned by the ineffectiveness of state mechanisms to protect the socio-economic interests of local residents and the absence of a clear national government policy on Rohingya refugees. Consequently, rejection of refugees has led to dehumanization and created an imaginary enemy for local residents to justify their rejection of refugees. Refugees are no longer perceived as human beings, but rather as threats, burdens, or even as savages who lack of human values. Applying the concept of imaginary enemy, this study shows that the community actions justified through the perception of refugees as an exaggerated threat which gradually escalated into fear.